The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1159/000023465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender, Body Composition and Birth Size on IGF-I in 7- and 8-Year-Old Children

Abstract: We investigated the relationship between IGF-I, gender, height, weight, body composition and birth size in 260 healthy 7- and 8-year-old children (139 females). All children were born term at Nepean Hospital, Western Sydney. Body composition was measured using dual energy X-ray absorptiometry. IGF-I levels were determined by radioimmunoassay. Girls had higher IGF-I levels than boys (20.2 ± 6.5 nmol/l compared to 15.9 ± 6.1 nmol/l, p < 0.001) but there was no correlation between age and IGF-I. IGF-I was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
5
25
1
Order By: Relevance
“…Physiological differences between the sexes regarding IGF-I metabolism exist. We found higher IGF-I concentrations in girls, which is consistent with results from other studies (Kaplowitz et al, 1982;Juul et al, 1997;Garnett et al, 1999;Kawai et al, 1999;Hoppe et al, 2004b, c;Bereket et al, 2006). The metabolism of IGF-I also seems to differ between boys and girls as it was found that 9-year-old boys excreted more urine (u) IGF-I per unit u growth hormone (GH) than the girls of the same age (Fall et al, 2000).…”
Section: 00supporting
confidence: 91%
“…Physiological differences between the sexes regarding IGF-I metabolism exist. We found higher IGF-I concentrations in girls, which is consistent with results from other studies (Kaplowitz et al, 1982;Juul et al, 1997;Garnett et al, 1999;Kawai et al, 1999;Hoppe et al, 2004b, c;Bereket et al, 2006). The metabolism of IGF-I also seems to differ between boys and girls as it was found that 9-year-old boys excreted more urine (u) IGF-I per unit u growth hormone (GH) than the girls of the same age (Fall et al, 2000).…”
Section: 00supporting
confidence: 91%
“…20 In our sample population, we have previously reported an Abdominal fat and birth size in children SP Garnett et al inverse relation between IGF-I concentrations at age 7=8 y and birth size -children with the lowest birth size and heaviest current weight had the highest IGF-I concentrations. 21 High concentrations may reflect persisting IGF-I resistance or alternatively be a response to adequate postnatal nutrition and hence be a feature of rapid postnatal growth. This seems less probable as catch up growth in response to low birth weight is generally complete by 3 y.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen of the boys were recruited from the Energy Expenditure Study, whose participants were originally recruited from state primary schools in western Sydney (19). An additional 23 boys were recruited from the Nepean Cohort Study, a birth cohort consisting of children born at a gestational age of Ͼ37 wk at Nepean Hospital in western Sydney between August 1989 and April 1990 (20). The 23 biologic mothers of these boys were also recruited to the study.…”
Section: Experimental Subjectsmentioning
confidence: 99%
“…Information on the birth weight, birth length, and ponderal index at birth [birth weight/birth length 3 ] of the sons was obtained from the records of the Nepean Cohort Study (20) or the personal health records of the boys, as appropriate.…”
Section: Anthropometrymentioning
confidence: 99%